Tissue shear as a cue for aligning planar polarity in the developing Drosophila wing - Su Ee Tan; David Strutt (Nature Communications)
Abstract Planar polarity establishment in epithelia requires interpretation of directional tissue-level information at cellular and molecular levels. Mechanical forces exerted during tissue morphogenesis are emerging as crucial tissue-level directional cues, yet the mechanisms by which they regulate planar polarity are poorly understood. Using the Drosophila pupal wing, we confirm that tissue stress promotes proximal-distal (PD) planar polarity alignment. Moreover, high tissue stress anisotropy can reduce the rate of accumulation and lower the stability on cell junctions of the core planar polarity protein Frizzled (Fz). Notably, under high tissue stress anisotropy, we see an increased gradient of cell flow, characterised by differential velocities across adjacent cell rows. This promotes core protein turnover at cell-cell contacts parallel to the flow direction, possibly via dissociation of transmembrane complexes by shear forces. We propose that gradients of cell flow play a critical role in establishing and maintaining PD-oriented polarity alignment in the developing pupal wing.